NILAI EDUKASI TERHADAP ANAK DALAM DONGENG DADONG PERKASA KARYA KABUL ASTUTI PADA SITUS WEB LET’S READ ASIA (KAJIAN SASTRA ANAK) - Monika Sari; Faika Burhan; Ali Mustopa (Seshiski: Southeast Journal of Language and Literary Studies, 2025)
The study entitled "Educational Values ​​for Children Through Fairy Tale Pesan Dalam Amplop by Yulina Tales on the Let's Read Asia Website (Children's Literature Study)" aims to describe how educational values ​​​​for children are conveyed through fairy tales on the Let's Read Asia website. This type of research is literature. The method used in this study is descriptive qualitative using a structural approach. The data in this study are all quotes in the form of words, sentences, and paragraphs found in the collection of fairy tale books on the Let's Read Asia website, which are considered to have educational values ​​​​of goodness for children and were published in 2024. The theory used is the theory put forward by Burhan Nurgiyantoro. The data sources in this study are fairy tales on the Let's Read Asia website published in 2024. The results of this study indicate that on the Let's Read Asia website there are several fairy tales that can provide educational value for children. Fairy Tale provides personal educational value in the form of emotional development values, imagination, development values, imagination development values, ethical and religious growth values.